Evaluasi e-Warong sebagai Upaya Pengentasan Kemiskinan di Kota Padang - Robi Eka Putra; Roni Ekha Putera (Pencerah Publishing, 2022)
Poverty is a complex problem experienced by various countries in the world, including Indonesia. The government has launched various poverty alleviation policies in Indonesia, one of which is through the Non-Cash Food Assistance (NCFA) policy with a program called e-Warong. The implementation of e-Warong in Padang City is known to be optimal, but needs to be improved in a few aspects in order to improve the quality of e-Warong to be perfect, so this study aims to evaluate the implementation of e-Warong as a poverty alleviation policy in Padang City. This study uses a qualitative approach with a descriptive method using secondary data sources. The results show that there have been no problems related to the integrity, reputation and credibility of e-Warong in Padang City. The conclusions of this research show that, to improve the quality of e-Warongs that operate in accordance with applicable regulations, close monitoring is required by third parties who are not related to structural positions from the city to the sub-district. monitoring by a private audit team can be a neutral and good addition to improving e-Warong in the city of Padang